Roles of Endogenous Melatonin in Resistance to Botrytis cinerea Infection in an Arabidopsis Model - Zhu, Ying; Guo, Miao-Jie; Song, Jian-Bo; Zhang, Shu-Yuan; Guo, Rui; Hou, Dai-Ru; Hao, Cheng-Ying; An, Hong-Li; Huang, Xuan (Frontiers in Plant Science, 2021)
Melatonin is an important bioactive molecule in plants. Two synthetases, ASMT and SNAT, are involved in the final two steps of melatonin synthesis. Melatonin clearly participates in responses to a variety of biotic and abiotic stresses in plants, but few studies have addressed the roles of endogenous melatonin in pathogen resistance. We investigated the role of endogenous melatonin in resistance to Botrytis cinerea infection in an Arabidopsis thaliana model system. Plant lines that overexpressed ASMT or SNAT through genetic manipulation showed upregulated expression of resistance genes PR1 and PR5, transcription factor gene WRKY33, and jasmonic acid (JA) defense pathway marker gene PDF1.2, and downregulated transcription factor gene MYC2 in JA signaling pathway. Higher melatonin content also enhanced activity of antioxidant enzymes SOD and POD, increased JA content, reduced plant disease symptoms, and reduced lesion size in leaves. These findings indicate that endogenous melatonin enhances plant resistance to B. cinerea infection. In contrast, ASMT and SNAT gene silencing lines showed opposite results, and were more susceptible to B. cinerea. Thus, it can be demonstrated that melatonin functions as an effective regulator of plant stress resistance at the genetic level. A schematic model is presented for its role in resistance to B. cinerea infection. Our findings also helped to elucidate the associated signal transduction pathways and interactions between melatonin and other plant hormones.